ISPCell: an interactive image-based streaming protocol for wireless cellular networks - Boukerche, Azzedine (2006)
Remote interaction with immersive 3D environments with acceptable level of quality of experience has become a challenging and interesting research topic. Due to the high data volume required to provide a rich experience to the user, robust and effcient wireless transport protocols have yet to be developed. On the other hand, cellular network technology has been widely deployed and is growing fast. The provision of remote interactive 3D environments over wireless cellular networks has several interesting applications, and it imposes some unsolved issues. Node mobility creates unstable bandwidth, which is a problem when providing smooth interaction to users. Although PDAs and cell phones are low resource devices, which makes it prohibitive to load and render entire virtual environments, they can still render images with relative ease. Based on this idea, this paper proposes a streaming system which relies on an image-based rendering approach, and is composed of several modules: a packetization scheme for images, an image-based rendering approach based on view morphing and its corresponding RTP payload format, and finally a bandwidth feedback mechanism and rate control. This paper illustrates some of the problems faced in this area, and provides a first step towards their solutions. We discuss our algorithms and present a set of simulation experiments to evaluate the performance of the proposed schemes.